Developing a Writing Assessment Instrument for English Students on Argumentative Essays - Nur Mukminatien; Raga Driyan Pratama; Impiani Zagoto; Ardhi Eka Fadilah; Risma Fahrul Amin; Suhono, Suhono; Erikson Saragih (Yayasan Payungi Smart Madani, 2025)
Writing argumentative essay poses a significant challenge for English students, who often struggle with expressing opinions, organizing ideas logically, and using appropriate language structures. Despite the importance of assessing writing skills at early stages, few reliable instruments exist that are specifically designed to evaluate argumentative essay. This study aims to develop a valid and reliable analytic rubric to assess students’ argumentative essay skills, focusing on six key components: clarity of thesis, organization and coherence, supporting evidence, argument development, language use, and vocabulary range. The research employed a design-based development approach, incorporating literature review, expert validation, and empirical testing. Content validity was established through expert judgment (S-CVI = 0.95), and the instrument was pilot-tested with 85 English students. Statistical analyses demonstrated high inter-rater reliability (ICC = 0.87) and strong internal consistency (Cronbach’s α = 0.89). Descriptive data revealed that while English students showed emerging abilities in thesis clarity and grammar, they struggled with supporting arguments and maintaining logical flow. The resulting rubric serves both as an assessment and instructional tool, helping educators diagnose English student needs and promote writing development. Unlike general-purpose rubrics or those designed for advanced English students, this rubric is specifically aligned with the challenges of early-stage academic writers. The study contributes to closing a gap in writing assessment tools and provides a practical resource for use in EFL classrooms